Sex, Knowledge, and Attitude of Stroke Survivors Attending Bebe Herbal Center on Risk Factors before and after Stroke - Polycarp U. Nwoha; Florence O. Okoro; Emmanuel C. Nwoha; Fidelia N. Chukwu; Chidinma O. Nwoha; Nkeiru C. Ogoko; Peace N. Nwoha; Chika A. Idaguko; Augustine U. Obi; Ezenna M. Agwu; Iyanu O. Ayoola; Sunday O. Osonwa; et al. (Stroke Research and Treatment)
Objective. The objective of this study was to investigate the extent stroke survivors who attended an herbal center knew of stroke risk factors and whether significant sex differences existed. Study Design. This was a cross-sectional study conducted from January to June 2018 at Bebe Herbal Center, and it involved two well-trained assistants who interviewed 149 first-time stroke survivors after consent and ethical approval were obtained. The survivors self-reported their knowledge, attitude, and beliefs on risk factors before and after stroke. Statistical Analyses. Means of continuous variables were compared using Student’s unpaired t-test, while categorical variables between males and the females were analyzed using Pearson’s chi-square test. P<0.05 was taken as significant. Results. Mean age of men (64.81±1.24 yrs) was significantly higher than that of women (61.39±1.42 yrs) (F=0.096, t=1.79, df=147; P<0.05). More men than women were 60 years and above while more women than men were below 60 years. Pearson’s chi-square test showed significant association of sex with education (χ2=12.31; df=3, P<0.006), occupation (χ2=23.65; df=4, P<0.001), alcohol intake (χ2=24.23; df=1; P<0.001), and smoking (χ2=9.823; df=1; P<0.001). The commonest risk factor suffered was hypertension (73.1%), followed by alcohol intake (59.1%), smoking (31.5%), and diabetes mellitus (26.7%); these affected men more than women. Male survivors unaware of their hypertensive status were more likely to have stroke than females, and age had a significant effect on the likelihood of developing a stroke; the same was occupation. Conclusions. These survivors suffered mainly from hypertension, triggered by psychosocial problems and diabetes mellitus; their stroke seemed fueled by unrecognized hypertension, unrecognized diabetes mellitus, ignorance of hyperlipidemia, and wide-scale belief in witchcraft as risk factor. Awareness programs in the third world should take these observations into consideration.